A crock or a pot, is that even a question? The prekmurje language from a sociolinguistic perspective - NEĆAK LÜK, ALBINA (Anali PAZU HD, 2023)
The article is linked to the Prekmurski pisker project. Drawing on the well-known dichotomy language: speach (langue: parole) the paper explores aspects of sociolinguistically conditioned choice and use of language(s) and language varieties (dialects, sociolects, idiolects) in everyday communication. It appoints to communication domains in which one or the other variety is appropriate or predominant. Attention is payed to the power relations between different language varieties that reflect the power relations between their speakers. Further on, the roles of language ideologies and language capital are discussed as factors influencing a person’s language choice and social position. The theoretical cues are illustrated by past and present experience of the Prekmurje language in contact with Hungarian and Slovenian high varieties.